Softwares educativos para alunos com deficiência intelectual: Estratégias utilizadas - Pedro, Ketilin Mayra [UNESP]; Chacon, Miguel Claudio Moriel [UNESP] (FapUNIFESP (SciELO), 2013)
The computer is present in everyday school life and using it with educational software must be mediated and planned in order for this resource to contribute to student learning, including those with intellectual disabilities (ID). Therefore, the aim was to propose specific computer activities for students with ID using educational software, and to quantify and analyze the technical and pedagogical strategies used. The participants were six students with ID enrolled in two public schools. To collect information we used observation protocols and a field journal. Data were analyzed quantitatively and qualitatively, based on the concepts of mediation and the zone of proximal development of cultural-historical theory. The results indicated that when the content developed in the computer classes were compatible with the proposed activities in the classroom, students with ID had opportunities to experience different activities that enable them to be successful. We noted that what enabled them to understand and correctly perform the proposed activities were the teaching strategies. Thus, we consider that technical knowledge about educational software and pedagogical knowledge about content that is being worked on, are insufficient to ensure that the proposed activity will contribute to the development of students with ID.
Educational software for students with intellectual disabilities: Selected strategies
Keywords: Educational software; Intellectual disability; Special education; Technical and pedagogical strategies